Environmental and Economic Efficiency of Recycling Industrial Waste in the Urals - Romanova, Olga A.; Sirotin, Dmitry V. (Economy of Regions, 2021)
A change in values of modern society has led to the transformation of economic development models based on the greening of industrial activities. This problem is particularly relevant for industrial regions, including the Urals, where environmental pressure mostly depends on the mining and metallurgical industry, which is a source of industrial waste. In this regard, we develop a methodology for assessing environmental and economic efficiency of technological solutions for processing industrial raw materials. The research methodology is based on the theory of industrial production efficiency, sustainable development theory and circular economy principles. To assess the efficiency, we applied the methods of comparative, structural and logical, economic and statistical analysis, as well as real options method. The comparative analysis revealed various trends in the generation, recycling, and accumulation of waste from mining and smelting activities in the whole Russia and the Middle Urals in the period 2013-2019. The industrial waste of the Urals is unique in terms of its multicomponent composition, including ferrous, non-ferrous and rare-earth metals. Thus, the real options method is optimal for assessing the efficiency of recycling industrial waste. The analysis of the approaches to the assessment of environmental and economic efficiency confirmed that traditional methods based on cost indicators are unreliable compared to the real options method. We described the main stages of this method and developed an algorithm for assessing environmental and economic efficiency of processing industrial raw materials. Further, we identified the real options for processing industrial resources of steel production that influence managerial decisions in a changing environment. Due to the versatility of the developed method, which considers both external uncertainty and requirements of advanced technologies, we recommend using this method for selecting effective investment projects aimed at processing industrial raw materials.